Lipidomic profiling of human serum enables detection of pancreatic cancer - Wolrab, Denise; Jirásko, Robert; Cífková, Eva; Höring, Marcus; Mei, Ding; Chocholoušková, Michaela; Peterka, Ondřej; Idkowiak, Jakub; Hrnčiarová, Tereza; Kuchař, Ladislav; Ahrends, Robert; Brumarová, Radana; et al. (Nature communications, 2022)
Pancreatic cancer has the worst prognosis among all cancers. Cancer screening of body fluids may improve the survival time prognosis of patients, who are often diagnosed too late at an incurable stage. Several studies report the dysregulation of lipid metabolism in tumor cells, suggesting that changes in the blood lipidome may accompany tumor growth. Here we show that the comprehensive mass spectrometric determination of a wide range of serum lipids reveals statistically significant differences between pancreatic cancer patients and healthy controls, as visualized by multivariate data analysis. Three phases of biomarker discovery research (discovery, qualification, and verification) are applied for 830 samples in total, which shows the dysregulation of some very long chain sphingomyelins, ceramides, and (lyso)phosphatidylcholines. The sensitivity and specificity to diagnose pancreatic cancer are over 90%, which outperforms CA 19-9, especially at an early stage, and is comparable to established diagnostic imaging methods. Furthermore, selected lipid species indicate a potential as prognostic biomarkers. Patients with pancreatic cancer have a poor prognosis, more research is required to identify the disease at an earlier stage. Here, the authors use lipid profiles of blood samples and show that they can distinguish patients with pancreatic cancer from healthy controls.